Development of a prototype early warning system for avian influenza in the EU based on risk‐mapping. Issue 12 (16th December 2022) - Gargallo, G.; Davies, J.G.; Faverjon, C.; Kampichler, C.; Baillie, S.R.; Cameron, A.; Robinson, R.A.; Sierdsema, H.
Abstract: Avian influenza (AI) is a highly contagious viral disease that affects primarily poultry and wild water birds. There have been continued outbreaks of highly pathogenic avian influenza (HPAI) in both poultry and wild bird flocks. We aim to capitalise on the existence of large citizen datasets on abundance and distribution of 12 wild bird species to assess spatial patterns in abundance and migration migratory routes to develop a prototype spatiotemporal risk assessment from HPAI outbreaks in wild bird populations. We undertake an initial analysis of wild bird abundance from the EuroBirdPortal dataset and movements from the EURING Databank to parameterise a risk model that estimates the weekly probability of having at least one wild bird infected with HPAI at the European Environment Agency (EEA) 50 x 50 km grid scale. The model is validated against the EMPRES‐i database of disease outbreaks. We provide proof of concept that such an approach is valuable and discuss current limitations and outline how the approach might be improved.